Marking Territory in a Transforming Neighbourhood: the Šančiai ‘Chair’ Parade - Lukošienė, Mykolė (Tautosakos darbai, 2020)
The aim of this paper is to analyse the manifestation of a local institutionalised community’s power and its resistance to gentrification in the Kaunas neighbourhood of Šančiai. Šančiai, during the last decade, is in the process of being rehabilitated, recreated and revisioned, by implementing new urban planning strategies and luxurious post-industrial urban visions. The manifestation of space production selected for the analysis presented in this paper is illustrated by the neighbourhood ‘Chair’ parade, where the power of the community and the resistance to mainstream gentrification manifests itself, applying the ritualistic event analysis proposed by Ronald L. Grimes.